Assessment of Collateral Status by Dynamic CT Angiography in Acute MCA Stroke: Timing of Acquisition and Relationship with Final Infarct Volume - van den Wijngaard, I.R.; Holswilder, G.; Wermer, M.J.H.; Boiten, J.; Algra, A.; Dippel, D.W.J.; Dankbaar, J.W.; Velthuis, B.K.; Boers, A.M.M.; Majoie, C.B.L.M.; van Walderveen, M.A.A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Dynamic CTA is a promising technique for visualization of collateral filling in patients with acute ischemic stroke. Our aim was to describe collateral filling with dynamic CTA and assess the relationship with infarct volume at follow-up.MATERIALS AND METHODS: We selected patients with acute ischemic stroke due to proximal MCA occlusion. Patients underwent NCCT, single-phase CTA, and whole-brain CT perfusion/dynamic CTA within 9 hours after stroke onset. For each patient, a detailed assessment of the extent and velocity of arterial filling was obtained. Poor radiologic outcome was defined as an infarct volume of ≥70 mL. The association between collateral score and follow-up infarct volume was analyzed with Poisson regression.RESULTS: Sixty-one patients with a mean age of 67 years were included. For all patients combined, the interval that contained the peak of arterial filling in both hemispheres was between 11 and 21 seconds after ICA contrast entry. Poor collateral status as assessed with dynamic CTA was more strongly associated with infarct volume of ≥70 mL (risk ratio, 1.9; 95% CI, 1.3–2.9) than with single-phase CTA (risk ratio, 1.4; 95% CI, 0.8–2.5). Four subgroups (good-versus-poor and fast-versus-slow collaterals) were analyzed separately; the results showed that compared with good and fast collaterals, a similar risk ratio was found for patients with good-but-slow collaterals (risk ratio, 1.3; 95% CI, 0.7–2.4).CONCLUSIONS: Dynamic CTA provides a more detailed assessment of collaterals than single-phase CTA and has a stronger relationship with infarct volume at follow-up. The extent of collateral flow is more important in determining tissue fate than the velocity of collateral filling. The timing of dynamic CTA acquisition in relation to intravenous contrast administration is critical for the optimal assessment of the extent of collaterals.CScollateral score